Analysis Of Profitability Before And After Changing The Interest Rate Of Other General Credit At Pt. Bank Sulselbar Centre Office Makassar - Yunita Nur Utami (IAIN Manado, 2018)
AbstractThe purpose of this research is to find out how to increase profitability before and after changes in other public credit interest rates at PT. Bank Sulselbar Makassar Head Office.The analytical method used is a paired sample T-test analysis of the comparison before and after the change in KUL credit interest rates at PT. Bank Sulselbar Makassar Head Office with the help of SPSS Version 21.0There is a significant difference in Profitability values before and after changes in other public loan rates. The results of the study show that the average profitability value before the change in other public credit interest rates is 32.38% and after the change in other public lending rates by 42.45%. This shows that there was an increase in the average value of profitability of 10.07% due to changes in other public lending rates.Based on the results of the research and discussion that has been done, it can be concluded that the results of the study indicate that there are significant positive differences in the value of profitability before and after changes in other public credit interest ratesKeywords: Profitability, Interest Rate